2010
DOI: 10.2215/cjn.03170509
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atrial Fibrillation and Its Predictors in Nondialysis Patients with Chronic Kidney Disease

Abstract: Background and objectives: Chronic kidney disease (CKD) increases systemic inflammation, which is implicated in development and maintenance of atrial fibrillation (AF); therefore, we hypothesized that the prevalence of AF would be increased among nondialysis patients with CKD. This study also reports independent predictors of the presence of AF in this population.Design, setting, participants, & measurements: A retrospective, cross-sectional analysis of 1010 consecutive nondialysis patients with CKD from two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
97
1
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 48 publications
8
97
1
7
Order By: Relevance
“…The estimated prevalence of AF in these patients is reported to be in the range of 7.0–27.0% [8,9]. Ananthapanyasut et al [10] reported a 21.2% (n = 214) incidence of AF among 1,010 nondialysis CKD patients. In addition, according to the Dialysis Outcomes and Practice Patterns Study (DOPPS), 12.5% (n = 2,188) of 17,513 dialysis patients had preexisting AF at baseline [11].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence of AF in these patients is reported to be in the range of 7.0–27.0% [8,9]. Ananthapanyasut et al [10] reported a 21.2% (n = 214) incidence of AF among 1,010 nondialysis CKD patients. In addition, according to the Dialysis Outcomes and Practice Patterns Study (DOPPS), 12.5% (n = 2,188) of 17,513 dialysis patients had preexisting AF at baseline [11].…”
Section: Discussionmentioning
confidence: 99%
“…11 Other studies also found increasing prevalence of AF with decreasing renal function. 12,13 In dialysisdependent patients with CKD stage 5, the prevalence of AF was estimated to range between 3.5% and 27%, depending on AF type.…”
Section: Ckd and Atrial Fibrillationmentioning
confidence: 99%
“…
I mpaired renal function is associated with a higher prevalence of atrial fibrillation (AF) [1][2][3] and with an increased risk of thromboembolic events in patients with nonvalvular AF. [4][5][6][7] Current guidelines recommend treatment with oral anticoagulants for AF patients at risk for stroke 8 ; however, impaired renal function also confers a substantially increased risk of major bleeding 9 and often contributes to underutilization of oral anticoagulation therapy in AF populations.
10,11
Clinical Perspective on p 970

Background-Renal impairment increases the risk of stroke and bleeding in patients with atrial fibrillation.

…”
mentioning
confidence: 99%